180k views
3 votes
Please help me thank you

Please help me thank you-example-1

1 Answer

3 votes

Answer:

x = 6

Explanation:

First, separate the problem into
-(2x)/(3) +9=(4x)/(3) - 3

Then, Subtract 9 from both sides of the equation.
-(2x)/(3) +9-9=(4)/(3) * x - 3-9

Simplify.
-(2x)/(3)=(4x)/(3)-12

Multiply 3 to each side, which will give you -2x = 4x - 36

Subtract 4x from each side -2x - 4x = 4x - 36x - 4x

Combine like terms: -6x = -36

Divide both sides by -6

Your answer should be 6

(sorry for the late answer)

User Tibor Blenessy
by
6.5k points